Medicines and hospitals brazilian health system: the impact of pharmacy and therapeutics committees - Rafael Santos Santana; Geovanna Cunha Cardoso; Iza Maria Fraga Lobo; Ellen Karla Chavez Vieira Koga; Wellington Barros da Silva (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2018)
This study aimed to analyze the economic and access impact, beyond the levels of essential drug lists of public hospitals after the establishment of Pharmacy and Therapeutics (P&T) committees. As a result, there has been a decrease of total number of medicines from a level of 716 items to 516 (27.8%). There was an increase in items of Brazilian Medicines List (13.6%), WHO Model List (10.5%) and medicines indicated by clinical guidelines (14.7%). Economic analysis shows that the costs of essential medicines list decrease in approximately 12%. The results obtained demonstrated the great potential of the P&T committee contribution in optimizing resources.